A Homogeneous Metal Oxide Catalyst Enhanced Solid–Solid Reaction in the Hydrogen Desorption of a Lithium–Hydrogen–Nitrogen System. Issue 3 (4th February 2014) - Zhang, Tengfei; Isobe, Shigehito; Wang, Yongming; Hashimoto, Naoyuki; Ohnuki, Somei
Abstract In this study, LiTi2O4 was synthesized as a possible catalyst in the Li‐N‐H system. The properties of hydrogen desorption in the Li‐N‐H system with a homogeneous catalyst have been investigated. The X‐ray diffraction and X‐ray photoelectron spectroscopy results indicated that the single phase of LiTi2O4 was successfully synthesized and it was stable in the sample after high energy ball‐milling and heat treatment. LiTi2O4 exhibited a catalytic effect in the Li‐N‐H system according to the thermogravimetry differential thermal analysis results. During dehydrogenation, a storage capacity of 5.7 wt % was obtained under moderate temperature. A sharp peak of thermal gas desorption mass spectrometry curve occurred at 227 °C. Furthermore, the catalytic mechanism of LiTi2O4 in the Li‐N‐H system was discussed in accordance with the experimental results.